A model for the performance based-budgeting of project-based organizations in the housing sector in Iran - Peyman Seyyedi; Mohammad Hasan Maleki; Seyyed Abbas Borhani; Omidali Adeli (اقتصاد شهری)
The foundation of every science based on a series of fixed principles. The budget, likewise an economic and administrative point of view, is based on the principles and foundations referred to as the budget principles. This research’s proposes to find the influencing factors on performance-based budgeting in project-based organizations and to determine the relationships between these factors to provide a model in the housing sector. A sample size equal to 15 experts who had relevant knowledge and experience in the field of project-based organizations in the housing sector were selected. For this purpose, 29 factors identified using the theme analysis technique, through interviews with experts and the theme analysis tool. Then, the factors screened using the binomial test method and expert questionnaire. Finally, the screened factors were analyzed using the Demetal-fuzzy technique. According to the net effect index obtained through the difference of effectiveness and effectiveness of factors, the research results showed four elements: systemic attitude, incentive and punishment system, employee training, organizational culture, which affect performance-based budgeting in project-based organizations.